2009
DOI: 10.1017/s0143385708000990
|View full text |Cite
|
Sign up to set email alerts
|

The solar Julia sets of basic quadratic Cremer polynomials

Abstract: Abstract. In general, little is known about the exact topological structure of Julia sets containing a Cremer point. In this paper we show that there exist quadratic Cremer Julia sets of positive area such that for a full Lebesgue measure set of angles the impressions are degenerate, the Julia set is connected im kleinen at the landing points of these rays, and these points are contained in no other impression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…The remaining basic uniCremer Julia sets are called red dwarf Julia sets. They can be defined as basic uniCremer Julia sets such that all impressions contain p. These notions have been introduced in [BO06a] and were further studied in [BBCO07] where it was shown that solar Julia sets of degree two, with positive Lebesgue measure, exist. The following lemma describes red dwarf Julia sets and complements Theorem 5.10.…”
Section: Introduction and Description Of The Resultsmentioning
confidence: 99%
“…The remaining basic uniCremer Julia sets are called red dwarf Julia sets. They can be defined as basic uniCremer Julia sets such that all impressions contain p. These notions have been introduced in [BO06a] and were further studied in [BBCO07] where it was shown that solar Julia sets of degree two, with positive Lebesgue measure, exist. The following lemma describes red dwarf Julia sets and complements Theorem 5.10.…”
Section: Introduction and Description Of The Resultsmentioning
confidence: 99%
“…However, the difference with our setup is that bubbles in the sense of Luo are Fatou components that are eventually mapped to a superattracting rather than a Siegel domain. Also, similar ideas are used in [BBCO10] where some quadratic Cremer Julia sets were studied by approximating them with Siegel Julia sets with specific properties.…”
Section: Polar Coordinates and Bubblesmentioning
confidence: 99%
“…2 is equal to the cross ratio of α 0 , α n , β 0 , β n . Then (9) z n = (1 − cosh(τ )) cosh δ n . 5 If the group generated by γ 0 and γ 1 is discrete then the set {cosh(δ n ) : n ∈ Z ≥2 } is discrete in C. The theorem follows from the following inductive relation on the sequence of δ n [12, p.67]: (10) cosh…”
Section: Complex Dynamics and Kleinian Groupsmentioning
confidence: 99%
“…Because of the rigidity of holomorphic functions, the theory of complex dynamics is rich in deep results: a complete combinatorial description of the structure of the Julia set of polynomials and (conjecturally) of the Mandelbrot set [53], application of the thermodynamical formalism to Julia sets (see for example the survey [55]) which allows to compute their Hausdorff dimensions, interplay with circle map dynamics and the theory of small divisors (for example [69]), as examples of realizations of unusual topologies as Julia sets (e.g. [9,57]) or of pathological dynamical systems [13].…”
Section: Introductionmentioning
confidence: 99%